BRAINSTORMING METHOD AND DISCUSSION TO INCREASING SOCIAL SKILL BY STUDENTS LEARNING ENVIRONMENT - Dian Ramahwati; Trisnaningsih Trisnaningsih; Pujiati Pujiati (Jurnal Studi Sosial / Journal of Social Studies, 2015)
The objectives of the research were to know the difference of the social skill improvement concerning the students learning environment among students interaction and between students teacher interaction that teaching learning used brainstorming method and discussion. This research used quasi experiment with factorial design. The interpretation sampling was probability sampling by using cluster random sampling. The collecting data technique used documentation, interviews, and social skill observation sheets. The first and sixth hypothesis testing were using two way variants while for second, third, fourth, fifth, an seventh were using t-test. The result of the research showed that there were difference increasing in social skills by observing the students learning environment seen from the students interaction among the students and between students and teacher who using brainstorming method and discussion.Penelitian ini bertujuan untuk mengetahui perbedaan peningkatan keterampilan sosial dengan memperhatikan lingkungan belajar siswa dilihat dari interaksi siswa dengan siswa dan interaksi siswa dengan guru yang pembelajarannnya menggunakan metode brainstorming dan diskusi. Metode penelitian yang digunakan adalah metode quasi experiment dengan desain faktorial. Teknik pengambilan sampel yaitu probability sampling dengan menggunakan cluster random sampling. Teknik pengumpulan data menggunakan dokumentasi, wawancara, dan lembar pengamatan keterampilan sosial. Pengujian hipotesis pertama dan keenam menggunakan analisis varian dua jalan sedangkan untuk hipotesis kedua, ketiga, keempat, kelima, dan ketujuh menggunakan t-test. Hasil penelitian menunjukkan bahwa terdapat perbedaan peningkatan keterampilan sosial dengan memperhatikan lingkungan belajar siswa dilihat dari interaksi siswa dengan siswa dan interaksi siswa dengan guru yang pembelajarannnya menggunakan metode brainstorming dan diskusi.Kata kunci: diskusi, keterampilan sosial, lingkungan belajar, metode brainstorming